Degradation effect of slope terracing on soil quality for Elaeis guineensis Jacq. (oil palm) cultivation - Hamdan, J.; Burnham, C. P.; B., Ruhana (Wiley, 2000)
A study was conducted to determine the effect of slope terracing on soil quality in some oil palm plantations in Peninsular Malaysia. Samples from three different deep terraced-saprolitic profiles of varying depth and geology were collected and analysed for their physicochemical properties and chemical fertility characteristics. Field observations showed that saprolites lying below the soil layers were either exposed directly or exposed near to the surface as a result of slope terracing to enable oil palm planting. The fertility status of the exposed saprolites, despite being less weathered, were poorer than the soils. Comparatively, they have high phosphorus retention capacity, lower net negative charge and thus lower cation retention capacity. The Al phytotoxic effect, however, was lower in the saprolites than in the soils. The saprolites' physical properties were characterized by massiveness and lack of structural development, which enables high water retention but which may not be available to plants. The transformation of rock into saprolites showed significant depletion of base cations from the profiles, instituting poor fertility status of saprolites in comparison to the respective soil layers. The saprolite materials were also found to be unsuitable for oil palm cultivation, with shallowness, fertility and poor drainage conditions being the major constraints.